The Singapore Writers Festival: Global Identity, Cultural Policy and the Post-Independence Literary Landscape - Tay, Eddie (SARE: Southeast Asian Review of English, 2017)
This paper takes its starting point the motivations, activities and subject positions of English literary authors in Singapore in relation to the cultural policy of the state as it pertains to literary production. It looks at the Singapore Writers Festival as a microcosm of the field of literary production in Singapore and explores how the identities of Singaporean authors are projected onto a global stage. Hence, the first part which focuses on the author's encounters with prominent Singaporean poet and anthologist. Alvin Pang, is anecdotal, to convey a sense of what has been happening in Singapore's contemporary literary landscape and to make the point that one of the ways to understand a national literary landscape- apart from close reading of the literary works - is to pay attention to the personalities, relationships and social networks within the context of literary events, educational initiatives to do with literature in relation to the state's cultural policy pertaining to the promotion of literary works among a local as well as a global audience.